Respuesta :

Answer:

Step-by-step explanation:

You have no grounds for making a statement like that.  There are a variety of reasons why you might not get immediate answers.  Be patient.

I will do the second part of this question (finding the first three numbers):

a(4) = a(3)*(-3) + 2 = -148, so a(3)*(-3) = -150 and a(3) = -50

a(3) = 50

a(2) = a(3)*(-3) + 2 = 50, so -3*a(3) = 48 and a(d) = -16

a(1) = a(2)*(-3) + 2 = -16, so a(2)*(-3) = -18 and a(1) = 6

The procedure for finding a(5), a(6) and a(7) is exactly the same.

ACCESS MORE